Preparation method of waterproof wear-resistant TPU (thermoplastic polyurethane) and application of waterproof wear-resistant TPU in zippers

By introducing polyhydroxy monomers and modified nanosilicon dioxide into polyurethane, the problems of poor water resistance, mechanical properties and wear resistance of polyurethane materials are solved, and the high-performance waterproof and wear resistance of TPU materials are achieved.

CN119752155AActive Publication Date: 2025-04-04YUMEI APPAREL TECH (DONGGUAN) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411955226.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Polyurethane materials have poor water resistance, poor mechanical properties and wear resistance.

Method used

By introducing polyhydroxy monomers as chain extenders into the polyurethane and blending and extruding with modified nanosilicon dioxide, the molecular chain cross-linking density and hydrophobicity of the polyurethane are improved.

Benefits of technology

The tensile, wear and waterproof properties of TPU materials are significantly improved, allowing them to perform better performance in applications such as zippers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215623370000021
    Figure BDA0005215623370000021
  • Figure BDA0005215623370000031
    Figure BDA0005215623370000031
  • Figure BDA0005215623370000071
    Figure BDA0005215623370000071
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane, and discloses a preparation method of waterproof wear-resistant TPU (thermoplastic polyurethane) and application of the waterproof wear-resistant TPU in zippers. The preparation method comprises the following steps: reacting polyester polyol with a diisocyanate monomer, adding 1, 4-butanediol and a polyhydroxy monomer, pouring into a mold, demolding, vulcanizing, mixing with modified silicon dioxide, extruding, and pelletizing to obtain the waterproof wear-resistant TPU. A large number of alkyl long chains are introduced to the surface of the nano silicon dioxide, so that the dispersity is improved, agglomeration is reduced, meanwhile, the compatibility with polyurethane is improved, the nano silicon dioxide is uniformly dispersed in a polyurethane matrix, and the tensile property, wear resistance and waterproof property of the TPU material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane, in particular to a preparation method of waterproof and wear-resistant TPU and application of the same in a zipper. Background Art

[0002] Polyurethane has good elasticity, heat resistance, oil resistance and aging resistance, and is widely used in shoe soles, zipper teeth, foam boards, packaging materials, etc. It is of great significance to fill and modify polyurethane to improve its mechanical strength, wear resistance, waterproofness and other properties. Common filler modifications include nano-silicon dioxide, carbon fiber, calcium carbonate, aluminum oxide, etc.

[0003] Nano silicon dioxide is a high-performance nano material, which is cheap and easy to obtain, has high mechanical strength, stable properties, and is easy to surface modify. It is widely used in polymer materials such as polyurethane, and usually requires the use of silane coupling agents, stearic acid, hexadecanol, polyethylene glycol, etc. The Chinese patent CN115852703A with a publication number discloses a modified nano silicon dioxide-reactive polyurethane cross-linked waterproofing agent and a preparation method. The modified nano silicon dioxide generated by modifying nano silicon dioxide with a long-chain alkyl silane coupling agent and an azide silane coupling agent is reacted with reactive polyurethane to obtain a modified nano silicon dioxide-reactive polyurethane cross-linked hydrophobic compound, which can be used in the waterproof finishing of cotton and chemical fiber fabrics. However, the patent does not improve the mechanical properties and wear resistance of polyurethane materials. Summary of the invention

[0004] The invention solves the problem that the polyurethane material has poor water resistance, mechanical properties and wear resistance.

[0005] Technical solution: A method for preparing waterproof and wear-resistant TPU:

[0006] Step S1, adding nano-silicon dioxide to water, ultrasonically dispersing, adding sodium hydroxide, stirring at 85-90° C. for 2-3 hours, then adding dilute hydrochloric acid to adjust the pH to 8-9, adding a polyhydroxy monomer, stirring for 2-5 hours, filtering, washing with n-butanol and water in turn, and drying to obtain modified silicon dioxide.

[0007] Step S2, mixing the dried polyester polyol and diisocyanate monomer, reacting at 65-75°C for 2-3h, then adding 1,4-butanediol and polyhydroxy monomer, stirring and mixing, and quickly pouring into a mold at 110-120°C, demolding after 1-2h, and then vulcanizing at 100-110°C for 12-18h, crushing the obtained polyurethane product, mixing it with modified silica in a mixer at a mass ratio of 100:(1-6), extruding it through an extruder, the extrusion temperature is 175-185°C, the screw speed is 100-150r / min, and pelletizing is performed to obtain a waterproof and wear-resistant TPU.

[0008] Preferably, the mass ratio of nano-silicon dioxide to polyhydroxy monomer in S1 is 100:(4-10).

[0009] Preferably, in step S2, the molar ratio of polyester polyol, diisocyanate, 1,4-butanediol and polyhydroxy monomer is 1:(2.8-3.2):(1.2-1.7):(0.3-0.8).

[0010] Preferably, the diisocyanate is toluene-2,4-diisocyanate or diphenylmethane-4,4'-diisocyanate.

[0011] Preferably, the method for preparing the polyhydroxy monomer comprises the following steps:

[0012] Step (1), add ethanolamine and alkyl chloride in a molar ratio of (1-1.1):1 to ethanol, heat to 75-80°C, condense and reflux for 24-30h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain alkylethanolamine. The reaction formula is:

[0013]

[0014] Step (2), add alkylethanolamine and 1,4-bis(oxyglycidyl)benzene in a molar ratio of (2-2.4):1 to ethanol, react at 50-65°C for 18-24h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain a polyhydroxy monomer. The reaction formula is:

[0015]

[0016] Preferably, the alkyl chloride in step (1) is any one of 1-chlorodecane, 1-chlorododecane, 1-chlorotetradecane and 1-chlorohexadecane.

[0017] Preferably, waterproof and wear-resistant TPU is used in zipper teeth.

[0018] Technical effect of the present invention: The present invention utilizes a polyhydroxy monomer to replace part of 1,4-butanediol as a chain extender, which contains multiple hydroxyl polymerization sites, thereby increasing the molecular chain crosslinking density of the polyurethane, which is beneficial to improving the tensile strength and reducing the wear volume. In addition, the polyhydroxy monomer contains a flexible alkyl long chain, which inhibits the accumulation of the hard segment of the polyurethane, has a certain plasticizing effect, improves the elongation at break, and enables the TPU to have better tensile properties and wear resistance.

[0019] The polyhydroxy monomer of the present invention contains a hydrophobic alkyl long chain, which is introduced into the polyurethane molecular chain, significantly improving the hydrophobicity and water contact angle of the TPU material, and is beneficial to improving the waterproof performance of the TPU material.

[0020] The polyhydroxy monomer of the invention contains multiple hydroxyl groups and has a strong interaction force with the surface of nano-silicon dioxide, thereby realizing surface modification of nano-silicon dioxide and introducing a large number of alkyl long chains on the surface, thereby improving dispersibility and reducing agglomeration. Then, the polyurethane is co-blended and extruded. Since the polyurethane also contains the same alkyl long chains, the compatibility between the nano-silicon dioxide and the polyurethane is improved, so that the nano-silicon dioxide is more evenly dispersed in the polyurethane matrix, and a better reinforcing effect can be exerted, thereby significantly improving the tensile properties and wear resistance of the TPU material. DETAILED DESCRIPTION

[0021] To facilitate those skilled in the art to understand the technical solution of the present invention, the technical solution of the present invention is further described in conjunction with specific embodiments.

[0022] Polyester polyol, molecular weight 2000, Xuzhou Yihuiyang New Materials Co., Ltd. Nano-silicon dioxide, average particle size 20nm, Guangzhou Hongwu Materials Technology Co., Ltd.

[0023] Embodiment 1:

[0024] (1) Add 40 mmol ethanolamine and 40 mmol 1-chlorohexadecane to 100 mL ethanol, heat to 80° C., condense and reflux for 24 h, rotary evaporate, separate and purify by silica gel column chromatography, and perform gradient elution with dichloromethane and methanol solution to obtain alkylethanolamine.

[0025] (2) Add 66 mmol alkylethanolamine and 30 mmol 1,4-bis(oxyglycidyl)benzene to 200 mL ethanol, react at 60° C. for 24 h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain a polyhydroxy monomer.

[0026] (3) Add 5 g of nano-silica to 200 mL of water, disperse by ultrasonic, add 40 mg of sodium hydroxide, stir at 90 ° C for 2 h, then add dilute hydrochloric acid to adjust the pH to 9, add 0.2 g of polyhydroxy monomer, stir for 2 h, filter, wash with n-butanol and water in turn, and dry to obtain modified silica.

[0027] (4) 100 mmol of dry polyester polyol and 300 mol of diphenylmethane-4,4'-diisocyanate were mixed, reacted at 65°C for 3 h, then 170 mmol of 1,4-butanediol and 30 mmol of polyhydroxy monomer were added, stirred and mixed, and then quickly poured into a mold at 110°C, demolded after 1 h, and then vulcanized at 110°C for 12 h. The obtained polyurethane product was crushed and mixed with modified silica in a mixer at a mass ratio of 100:1, extruded through a twin-screw extruder at an extrusion temperature of 180°C and a screw speed of 150 r / min, and pelletized to obtain waterproof and wear-resistant TPU.

[0028] Embodiment 2:

[0029] (1) Add 40 mmol ethanolamine and 40 mmol 1-chlorodecane to 150 mL ethanol, heat to 75°C, condense and reflux for 30 hours, rotary evaporate, separate and purify by silica gel column chromatography, and use dichloromethane and methanol solution for gradient elution to obtain alkylethanolamine.

[0030] (2) Add 60 mmol alkylethanolamine and 30 mmol 1,4-bis(oxyglycidyl)benzene to 200 mL ethanol, react at 50° C. for 24 h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain a polyhydroxy monomer.

[0031] (3) Add 5 g of nano-silica to 250 mL of water, disperse by ultrasonic, add 52 mg of sodium hydroxide, stir at 85 ° C for 3 h, then add dilute hydrochloric acid to adjust the pH to 8, add 0.35 g of polyhydroxy monomer, stir for 5 h, filter, wash with n-butanol and water in turn, and dry to obtain modified silica.

[0032] (4) 100 mmol of dry polyester polyol and 280 mol of diphenylmethane-4,4'-diisocyanate were mixed, reacted at 65°C for 3 h, then 140 mmol of 1,4-butanediol and 60 mmol of polyhydroxy monomer were added, stirred and mixed, and then quickly poured into a mold at 110°C, demolded after 2 h, and then vulcanized at 100°C for 18 h. The obtained polyurethane product was crushed and mixed with modified silica in a mixer at a mass ratio of 100:3, extruded through a twin-screw extruder at an extrusion temperature of 175°C and a screw speed of 100 r / min, and pelletized to obtain waterproof and wear-resistant TPU.

[0033] Embodiment 3:

[0034] (1) Add 44 mmol ethanolamine and 40 mmol 1-chlorotetradecane to 150 mL ethanol, heat to 80° C., condense and reflux for 24 h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain alkylethanolamine.

[0035] (2) Add 72 mmol alkylethanolamine and 30 mmol 1,4-bis(oxyglycidyl)benzene to 300 mL ethanol, react at 65° C. for 18 h, rotary evaporate, separate and purify by silica gel column chromatography, and gradient elute with dichloromethane and methanol solution to obtain a polyhydroxy monomer.

[0036] (3) Add 5 g of nano-silica to 250 mL of water, disperse by ultrasonication, add 65 mg of sodium hydroxide, stir at 90 ° C for 2 h, then add dilute hydrochloric acid to adjust the pH to 9, add 0.5 g of polyhydroxy monomer, stir for 5 h, filter, wash with n-butanol and water in turn, and dry to obtain modified silica.

[0037] (4) Mix 100 mmol of dry polyester polyol and 320 mol of toluene-2,4-diisocyanate, react at 65-75°C for 2-3 hours, then add 120 mmol of 1,4-butanediol and 80 mmol of polyhydroxy monomer, stir and mix, and quickly pour into a mold at 120°C, demould after 1 hour, and then vulcanize at 100°C for 18 hours. The obtained polyurethane product is crushed and mixed with modified silica in a mixer at a mass ratio of 100:6, and extruded through a twin-screw extruder at an extrusion temperature of 185°C and a screw speed of 100 r / min. Pelletize to obtain waterproof and wear-resistant TPU.

[0038] Comparative Example 1:

[0039] (1) 100 mmol of dried polyester polyol and 300 mol of diphenylmethane-4,4'-diisocyanate were mixed, reacted at 65°C for 3 h, then 200 mmol of 1,4-butanediol was added, stirred and mixed, and then quickly poured into a mold at 110°C, demolded after 1 h, and then vulcanized at 110°C for 12 h. The obtained polyurethane product was crushed, mixed with nano-silicon dioxide in a mixer at a mass ratio of 100:1, extruded through a twin-screw extruder, the extrusion temperature was 180°C, the screw speed was 150 r / min, and pelletized to obtain waterproof and wear-resistant TPU.

[0040] Comparative Example 2:

[0041] (1) 100 mmol of dried polyester polyol and 300 mol of diphenylmethane-4,4'-diisocyanate were mixed and reacted at 65°C for 3 h, then 170 mmol of 1,4-butanediol and 30 mmol of polyhydroxy monomer (prepared in Example 1) were added, stirred and mixed, and then quickly poured into a mold at 110°C, demolded after 1 h, and then vulcanized at 110°C for 12 h. The obtained polyurethane product was crushed and mixed with nano-silicon dioxide in a mixer at a mass ratio of 100:1, extruded through a twin-screw extruder at an extrusion temperature of 180°C and a screw speed of 150 r / min, and pelletized to obtain a waterproof and wear-resistant TPU.

[0042] Comparative Example 3:

[0043] (4) 100 mmol of dried polyester polyol and 300 mol of diphenylmethane-4,4'-diisocyanate were mixed, reacted at 65°C for 3 h, and then 200 mmol of 1,4-butanediol was added. After stirring and mixing, the mixture was quickly poured into a mold at 110°C, demolded after 1 h, and then vulcanized at 110°C for 12 h. The obtained polyurethane product was crushed and mixed with modified silica (prepared in Example 1) in a mixer at a mass ratio of 100:1, extruded through a twin-screw extruder at an extrusion temperature of 180°C and a screw speed of 150 r / min, and pelletized to obtain a waterproof and wear-resistant TPU.

[0044] Comparative Example 4:

[0045] (1) Add 5 g of nano-silica to 200 mL of water, disperse by ultrasonication, add 40 mg of sodium hydroxide, stir at 90 ° C for 2 h, then add dilute hydrochloric acid to adjust the pH to 9, add 0.2 g of 1-hexadecanol, stir for 2 h, filter, wash with n-butanol and water in turn, and dry to obtain modified silica.

[0046] (2) 100 mmol of dried polyester polyol and 300 mol of diphenylmethane-4,4'-diisocyanate were mixed, reacted at 65°C for 3 h, and then 170 mmol of 1,4-butanediol and 30 mmol of polyhydroxy monomer (prepared by Example 1) were added. After stirring and mixing, the mixture was rapidly poured into a mold at 110°C, demolded after 1 h, and then vulcanized at 110°C for 12 h. The obtained polyurethane product was crushed and mixed with modified silica in a mixer at a mass ratio of 100:1, extruded through a twin-screw extruder at an extrusion temperature of 180°C and a screw speed of 150 r / min, and pelletized to obtain a waterproof and wear-resistant TPU.

[0047] The TPU was molded in a flat vulcanizer at 10 MPa and 180°C for 10 min to prepare a test specimen.

[0048] The tensile properties were tested according to GB / T 528-2009. The Akron abrasion volume and wear resistance were tested according to GB / T 1689-2014.

[0049] The sample was pressed into a film sample and the water contact angle was tested according to GB / T 30693-2014 standard.

[0050] Table 1 TPU performance test

[0051]

[0052] In Comparative Example 1, 1,4-butanediol is used as a chain extender, and the obtained polyurethane is co-extruded with nano-silicon dioxide. The tensile strength and elongation at break of the TPU material are low, the Akron wear volume is large, the tensile performance and wear resistance are poor, and the water contact angle is small, and the water resistance and waterproofing are poor. This is mainly because the nano-silicon dioxide has poor dispersibility, is easy to agglomerate in the polyurethane matrix, and the compatibility of nano-silicon dioxide and polyurethane is poor, resulting in poor tensile performance and wear resistance of TPU.

[0053] Comparative Example 2 uses polyhydroxy monomers to replace part of 1,4-butanediol as a chain extender, and the tensile strength and elongation at break of the obtained TPU material are increased, the Akron wear volume is reduced, and the water contact angle is increased, and the tensile properties, wear resistance and waterproof properties are improved. This is because the polyhydroxy monomer contains multiple hydroxyl polymerization sites, which increases the molecular chain cross-linking density of the polyurethane, which is beneficial to improve the tensile strength and reduce the wear volume, and the polyhydroxy monomer contains flexible alkyl long chains, which inhibits the accumulation of the hard segment of the polyurethane and has a certain plasticizing effect, thereby improving the elongation at break, making the TPU have better tensile properties and wear resistance, and the alkyl long chain has a strong hydrophobicity, which is introduced into the polyurethane molecular chain, significantly improving the hydrophobicity and water contact angle of the TPU material, which is beneficial to improve the waterproof performance.

[0054] Compared with Comparative Example 1, after the nano-silicon dioxide in Comparative Example 3 is modified with a polyhydroxy monomer, its dispersibility is improved, and agglomeration is reduced, which is beneficial to improving the tensile properties and wear resistance of the TPU material.

[0055] In Example 1-3, polyhydroxy monomers are used to replace part of 1,4-butanediol as chain extenders, and the TPU obtained by co-extrusion with modified silica has better tensile properties and wear resistance. This is because polyurethane contains long alkyl chains, and the surface of modified silica also contains the same long alkyl chains, thereby improving the compatibility between nano-silica and polyurethane, making nano-silica more evenly dispersed in the polyurethane matrix, which can play a better reinforcing role, further improving the tensile properties and wear resistance of TPU materials. And it shows good waterproof performance.

[0056] Compared with Example 1, Comparative Example 4 uses hexadecanol as a modifier to perform surface modification on nano-silica, introduces long alkyl chains on the surface, and improves its compatibility with polyurethane. The tensile properties and wear resistance of the polyurethane are good, but the tensile strength and elongation at break are lower than those of Example 1, and the wear volume is higher than that of Example 1. This is mainly because hexadecanol contains only one hydroxyl group, and the interaction force with the surface of nano-silica is low, and the modification effect is not good. The polyhydroxy monomer of Example 1 contains multiple hydroxyl groups, and the interaction force with the surface of nano-silica is stronger, and the modification effect is very good. More long alkyl chains can be introduced on the surface of nano-silica to further enhance the compatibility with polyurethane, thereby exerting a better reinforcement effect.

[0057] The technical solution of the present invention is described above in combination with the embodiments. Obviously, the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for preparing waterproof and wear-resistant TPU, characterized in that: The steps include: Step S1, adding nano-silicon dioxide to water, ultrasonically dispersing, adding sodium hydroxide, stirring at 85-90° C. for 2-3 hours, then adding dilute hydrochloric acid to adjust the pH to 8-9, adding a polyhydroxy monomer, stirring for 2-5 hours, filtering, washing, and drying to obtain modified silicon dioxide; Step S2, mixing the dried polyester polyol and diisocyanate monomer, reacting at 65-75° C. for 2-3 hours, then adding 1,4-butanediol and polyhydroxy monomer, stirring and mixing, pouring into a mold at 110-120° C., demolding after 1-2 hours, and then vulcanizing at 100-110° C. for 12-18 hours, crushing the obtained polyurethane product, mixing it with modified silica in a mixer at a mass ratio of 100:(1-6), extruding through an extruder, and pelletizing to obtain a waterproof and wear-resistant TPU.

2. The method for preparing the waterproof and wear-resistant TPU according to claim 1, characterized in that: In the step S1, the mass ratio of nano-silicon dioxide to polyhydroxy monomer is 100:(4-10).

3. The method for preparing the waterproof and wear-resistant TPU according to claim 1, characterized in that: In the step S2, the molar ratio of polyester polyol, diisocyanate, 1,4-butanediol and polyhydroxy monomer is 1:(2.8-3.2):(1.2-1.7):(0.3-0.8).

4. The method for preparing the waterproof and wear-resistant TPU according to claim 3, characterized in that: The diisocyanate is toluene-2,4-diisocyanate or diphenylmethane-4,4'-diisocyanate.

5. The method for preparing the waterproof and wear-resistant TPU according to claim 3, characterized in that: The preparation method of the polyhydroxy monomer comprises the following steps: Step (1), adding ethanolamine and alkyl chloride in a molar ratio of (1-1.1):1 to ethanol, heating to 75-80° C., condensing and refluxing for 24-30 hours, rotary evaporation, and separation and purification by silica gel column chromatography to obtain alkylethanolamine; Step (2), adding alkylethanolamine and 1,4-bis(oxyglycidyl)benzene to ethanol, rotary evaporation after the reaction, and separation and purification by silica gel column chromatography to obtain a polyhydroxy monomer.

6. The method for preparing the waterproof and wear-resistant TPU according to claim 5, characterized in that: In the step (1), the alkyl chloride is any one of 1-chlorodecane, 1-chlorododecane, 1-chlorotetradecane and 1-chlorohexadecane.

7. The method for preparing the waterproof and wear-resistant TPU according to claim 5, characterized in that: In the step (2), the molar ratio of alkylethanolamine to 1,4-bis(oxyglycidyl)benzene is (2-2.4):

1.

8. The method for preparing the waterproof and wear-resistant TPU according to claim 5, characterized in that: The reaction temperature in step (2) is 50-65°C and the reaction time is 18-24h.

9. The method for preparing the waterproof and wear-resistant TPU according to claim 1, characterized in that: In step S2, the extrusion temperature of the twin-screw extruder is 175-185° C., and the screw speed is 100-150 r / min.

10. Use of the waterproof and wear-resistant TPU obtained by the preparation method according to any one of claims 1 to 9 in a zipper.

Citation Information

Patent Citations

  • Modified nano silicon dioxide-reactive polyurethane cross-linked water repellent agent and preparation method thereof

    CN115852703A

  • Preparation method of oxidized graphene modified water-based alcohol acid anticorrosion emulsion

    CN107987264A

  • Low-density high-strength high-yellowing-resistant TPU for soles, and preparation method thereof

    CN110627983A

  • Low-density, high-wear-resistance and high-skid-resistance TPU for shoe outsole and preparation method thereof

    CN110982248A

  • Antibacterial and deodorant composition and preparation method thereof

    CN116322807A